2018
DOI: 10.1371/journal.pone.0204690
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of anthocyanin accumulation-related genes in pepper fruits using a combination of SLAF-seq and BSA

Abstract: Anthocyanins have significant functions in stress tolerance in pepper (Capsicum annuum L.) and also benefit human health. Nevertheless, the key structural genes and regulatory genes involved in anthocyanin accumulation in pepper fruits are still not well understood and fine mapped. For the present study, 383 F2 plants from a cross between the green-fruited C. annuum line Z5 and the purple-fruited line Z6 was developed. Two separate bulked DNA pools were constructed with DNAs extracted from either 37 plants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
4
15
0
Order By: Relevance
“…Notably, the average distance between adjacent markers found here was also less than in a previously reported SLAF-seq genetic map of L. vannamei (0.75 cM) [30], possibly because we used a larger sample size and a greater sequencing depth. However, the number of LGs in the genetic map of L. vannamei in this study (44) was consistent with the number of LGs in the previously reported genetic map of L. vannamei [30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, the average distance between adjacent markers found here was also less than in a previously reported SLAF-seq genetic map of L. vannamei (0.75 cM) [30], possibly because we used a larger sample size and a greater sequencing depth. However, the number of LGs in the genetic map of L. vannamei in this study (44) was consistent with the number of LGs in the previously reported genetic map of L. vannamei [30].…”
Section: Discussionsupporting
confidence: 92%
“…The genome of L. vannamei is large (~2.45 Gb) [32]. Whole-genome deep resequencing is relatively costly for large genomes and is often not necessary for gene/QTL mapping [43,44]. In this study, we constructed a high-density genetic map of L. vannamei using SLAF-seq, which is an effective method by which to discover large numbers of SNPs and to perform large-scale genotyping [20].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the average distance between adjacent markers found here was also less than in a previously reported SLAF-seq genetic map of L. vannamei (0.75 cM) [30], possibly because a larger sample size and a greater sequencing depth were used. However, the number of LGs in the genetic map of L. vannamei in this study (44) was consistent with the number of LGs in the previously reported genetic map of L. vannamei [30]. This indicated that L. vannamei had 44 chromosomes.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the average distance between adjacent markers found here was also less than in a previously reported SLAF-seq genetic map of L. vannamei (0.75 cM) [30], possibly because a larger sample size and a greater sequencing depth were used. However, the number of LGs in the genetic map of L. vannamei in this study (44) was consistent with the number of LGs in the previously reported genetic map of L. vannamei [30]. This indicated that L. vannamei had 44 chromosomes, which was rst reported by CamposRamos [53].…”
Section: Discussionsupporting
confidence: 92%